Spatial Analysis of Landscape Suitability of Ambon City for Settlement Using Geographic Information System - Latue, Philia Christi; Rakuasa, Heinrich (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
This study analyzes the suitability of Ambon city landscape for settlement development purposes. This research utilizes spatial analysis to evaluate the characteristics of the terrain shape and Land Use Territory (WTU) in the context of settlement suitability. This research uses DEM (Digital Elevation Model) to generate slope and elevation or altitude which is later used to create terrain shape map and business land area map. Making landscape suitability using the weighted sum overlay method. The results showed that the landscape in Ambon City that is suitable for settlement development is 30,456.94 ha and the unsuitable one has an area of 16,890.38 ha. The results of this study provide insight into the most suitable locations for settlements based on physical and environmental factors. The results of this study are expected to support sustainable urban planning in Ambon by considering aspects of landscape suitability.